2018
DOI: 10.1038/emm.2017.285
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation disrupts the lacrimal system and induces dry eye disease

Abstract: Sleep deficiency is a common public health problem associated with many diseases, such as obesity and cardiovascular disease. In this study, we established a sleep deprivation (SD) mouse model using a ‘stick over water’ method and observed the effect of sleep deficiency on ocular surface health. We found that SD decreased aqueous tear secretion; increased corneal epithelial cell defects, corneal sensitivity, and apoptosis; and induced squamous metaplasia of the corneal epithelium. These pathological changes mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 39 publications
3
71
2
Order By: Relevance
“…In this study, we used an SD mouse model to mimic the DED induced by sleep deficiency. A previous study found that the pathological changes affecting SDE mice include decreased aqueous tear secretion, defects and squamous metaplasia of corneal epithelial cells, and corneal barrier function damage (Li et al, 2018). We did not find obvious corneal inflammation after 10 days of SD.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…In this study, we used an SD mouse model to mimic the DED induced by sleep deficiency. A previous study found that the pathological changes affecting SDE mice include decreased aqueous tear secretion, defects and squamous metaplasia of corneal epithelial cells, and corneal barrier function damage (Li et al, 2018). We did not find obvious corneal inflammation after 10 days of SD.…”
Section: Discussioncontrasting
confidence: 62%
“…The periodic acid-Schiff staining results indicated that SD slightly increased the mean number of goblet cells, compared with control group (101 ± 7 vs. 90 ± 25), but the difference was not statistically significant ( Figures 8A, B). This change in goblet cells is an adaptive response to the decreased tear secretion at the early stage of DED (Li et al, 2018). Application of PEA markedly increased conjunctival goblet cell density (144 ± 29) ( Figure 8C).…”
Section: Pea Increased the Number Of Conjunctival Goblet Cells And Tementioning
confidence: 89%
See 3 more Smart Citations